Concept of forms and legal functions of the functioning of the control system and against the interaction of the higher authorities of the state authority - Малышкина, Наталья Олеговна (Problems of legality, 2018)
Different approaches to the understanding of the content of the form and legal means of functioning of the system of checks and balances in the relations between the higher state bodies are analyzed in the work. It is concluded that in practice not only the distribution of powers of the higher state authorities is important for the achievement of the goals defined in the Constitution of Ukraine, but also their interaction, which necessarily takes place in clearly defined legal forms with the use of legal means. Legal means and forms of functioning of the system of checks and balances in the interaction of higher authorities are part of the law as a whole in its instrumental sense and in its unity form legal mechanisms that act to achieve socially meaningful results. Implementation by the supreme bodies of state power of their constitutional powers in relation to one another is actually the legal form of their interaction. Such interaction not only can not exist without certain tools, legal means, but only happens when they are implemented and in order to achieve the goals and objectives of the state, and is actually an external manifestation of a comprehensive system of checks and balances, which is enshrined in the Constitution and laws of Ukraine. It is also concluded that the system of general and special (legal) conditions, special (legal) means, forms, mechanisms of proper implementation of the competence and powers of the highest bodies of state power of Ukraine, defined by the constitution of Ukraine and the laws of Ukraine, during their interaction with each other acts as a guarantee of a system of checks and balances in the relations of the highest bodies of state power in Ukraine. In real life, the same legal means and legal forms can simultaneously serve as ensuring the proper organization of the exercise of powers by the highest state authorities, taking into account the system of checks and balances enshrined in the current legislation, as well as guaranteeing the protection and inviolability of the constitutional law as bodies of state power and citizens from any encroachment, give it a real character. The absence or ineffectiveness of existing legal remedies (guarantees) for the functioning of the system of checks and balances, the exercise of powers by the highest state authorities without observance of a clearly defined legal form usually creates instability of state-power relations, may lead to restrictions of rights, non-fulfillment of duties, violation of the rules of the current legislation by abuse or abuse of authority.